2013
DOI: 10.1111/jphp.12016
|View full text |Cite
|
Sign up to set email alerts
|

Crocin, a dietary colorant mitigates cyclophosphamide-induced organ toxicity by modulating antioxidant status and inflammatory cytokines

Abstract: The results obtained suggest the protective nature of crocin against CP-induced oxidative damage/inflammation and organ toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 35 publications
(47 reference statements)
6
38
0
1
Order By: Relevance
“…Nowadays, increased rates of cure or remission obtained by anticancer treatments (29,30) @ C I C E d i z i o n i I n t e r n a z i o n a l i fects on numerous cancer types including those with high incidence in women of reproductive age, they may represent good candidates as protective compounds against chemo-induced gonadotoxicity (21,31). In this context, present findings represent the first evidence for the chemoprotective potential of natural antioxidant compounds against ovarian cytotoxicity and are consistent with previous results in the male gonad and other organs in mice (21,32,33). It is known that PFs are in a quiescent state by fine tuning of the PI3K/PTEN/Akt-FOXO3a pathway (17).…”
Section: Discussionsupporting
confidence: 80%
“…Nowadays, increased rates of cure or remission obtained by anticancer treatments (29,30) @ C I C E d i z i o n i I n t e r n a z i o n a l i fects on numerous cancer types including those with high incidence in women of reproductive age, they may represent good candidates as protective compounds against chemo-induced gonadotoxicity (21,31). In this context, present findings represent the first evidence for the chemoprotective potential of natural antioxidant compounds against ovarian cytotoxicity and are consistent with previous results in the male gonad and other organs in mice (21,32,33). It is known that PFs are in a quiescent state by fine tuning of the PI3K/PTEN/Akt-FOXO3a pathway (17).…”
Section: Discussionsupporting
confidence: 80%
“…It was observed that there is an significant rise in the level of TAC with administered CYP plus HT. These may imply that overproduction of reactive oxygen species could be reduced by the HT, in the same line, other studies indicated a decrease in the antioxidantive enzyme activity is a consequence of raised oxidative stress in the heart tissue [34,37]. This results are consistent with numerous researches [11,16,38].…”
Section: Tocsupporting
confidence: 82%
“…The GSH level was found significantly increased in the 25, 50, 100 mg/kg HT-administered groups compared with group of CYP. In the same line it was observed that HT following CYP treatment protected the normal GSH level [34]. Paralel to our results, Liu et al [25] demonstrated the highest MDA level and the lowest GSH level in the CYP group compared to control.…”
Section: Tocsupporting
confidence: 77%
See 1 more Smart Citation
“…Νεότερες μελέτες έδειξαν επίσης πως ο κρόκος προστατεύει από τις τοξικές επιδράσεις και άλλων αντινεοπλασματικών φαρμάκων όπως της κυκλοφωσφαμίδης και της μιτομυκίνης-C. Ειδικότερα η χορήγηση κρόκου σε πειραματόζωα ανέστειλε τις βλάβες που προκαλούν αυτοί οι αλκυλιωτικοί παράγοντες στο DNA κυττάρων του μυελού των οστών, ενώ σε πιο πρόσφατη μελέτη η χορήγηση κροκίνης σε επίμυες (10 mg/kg po για 6 ημέρες) ανταγωνίστηκε σημαντικά την νεφροτοξική και ηπατοτοξική δράση της κυκλοφωσφαμίδης, μέσω αντιοξειδωτικών μηχανισμών (Premkumar et al, 2006;Jnaneshwari et al, 2013).…”
Section: βιολογικές δράσειςunclassified